Analysis Of Geomorphology Using the Coastal Vulnerability Index Method on the Coast of Prancak Village, Bangkalan Regency, Indonesia - Zakariyya, Muhammad Zaiki; Ilham Cahya; Wicaksono, Ashari; Lailiyah, Inayatul (Maritime Park: Journal of Maritime Technology and Society, 2026)
Coastal areas are highly dynamic environments facing increasing threats from both natural processes and human activities, such as coastal erosion, sea level rise, and land use changes. Prancak Village is one such coastal area vulnerable to geomorphological changes. This study aims to assess coastal vulnerability through geomorphological analysis using the Coastal Vulnerability Index (CVI) method. Data were collected from primary and secondary sources, including satellite imagery, field surveys, digital elevation models (DEMs), and data from relevant agencies. The analyzed parameters comprised coastal morphology, beach slope, shoreline change, wave height, and tidal range. The CVI calculation yielded a value of 6.93, which falls within the 5.8–10.06 range classified as “low vulnerability” (20–40% vulnerability level), indicating that the study site has relatively low susceptibility to the physical factors assessed Although the overall index is low, local physical dynamics still pose risks in certain areas, confirming that geomorphology and coastal ecosystem conditions are more decisive in determining vulnerability than oceanographic parameters such as wave height.